PROSEDUR PENETAPAN TERSANGKA PASCA DIPERLUASNYA OBJEK PRAPERADILAN: STUDI KASUS PUTUSAN NOMOR 01/PID.PRA/2022/PN. JBG - Savitri, Winny; Simangunsong, Frans (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Pretrial agencies aim to monitor the acts of coercive efforts made by investigators or public prosecutors against suspects. Along with the development of the pretrial object in terms of the determination of suspects regulated in the Constitutional Court Decision Number 21/PUU-XII/2014 dated April 28, 2015 which decided the determination of suspects as pretrial objects has created its own legal problems. Especially on the difficulty of distinguishing between proof for pretrial and proof for the subject matter. With the acceptance of the determination of the suspect as a pretrial object, the pretrial judge must test the evidence as a minimum requirement for the determination of the suspect in the pretrial hearing process. The aim of this research is to realize how the procedure for determining suspects after the expansion of pretrial objects. This study applied normative juridical methods based on primary and secondary data through literature studies. This research result is that the procedure for determining suspects must be complemented by an examination of potential suspects with the need for laws and regulations as implementers of the Constitutional Court Decision Number 21 / PUU-XII / 2014 to be used as guidelines by law enforcement officials, namely investigators, both prosecutors and police in determining suspects so that there is no multi-interpretation in phrase 2 (two) evidence and accompanied by examination of potential suspects